Enhancing the Initial Acceleration Performance of Elite Rugby Backs. Part II: Insights From Multiple Longitudinal Individual-Specific Case-Study Interventions - Neil Bezodis (International Journal of Sports Physiology and Performance)
Purpose: This study implemented 18-week individual-specific sprint acceleration training interventions in elite male rugby backs based on their predetermined individual technical needs and evaluated the effectiveness of these interventions. Methods: Individual-specific interventions were prescribed to 5 elite rugby backs over an 18-week period. Interventions were informed by the relationships between individual technique strategies and initial acceleration performance, and their strength-based capabilities. Individual-specific changes in technique and initial acceleration performance were measured at multiple time points across the intervention period and compared with 3 control participants who underwent their normal training. Results: Of the technique variables intentionally targeted during the intervention period, moderate to very large (|d| = 0.93–3.99) meaningful changes were observed in the participants who received an individual-specific intervention but not in control participants. Resultant changes to the intervention participants’ whole-body kinematic strategies were broadly consistent with the intended changes. Moderate to very large (|d| = 1.11–2.82) improvements in initial acceleration performance were observed in participants receiving individual-specific technical interventions but not in the control participants or the participant who received an individual-specific strength intervention. Conclusions: Individual-specific technical interventions were more effective in manipulating aspects of acceleration technique and performance compared with the traditional “one-size-fits-all” approach adopted by the control participants. This study provides a novel, evidence-based approach for applied practitioners working to individualize sprint-based practices to enhance acceleration performance.